Hemophagocytic inflammatory syndrome in ADA-SCID: report of two cases and literature review - Fratini, Elena Sophia; Migliavacca, Maddalena; Barzaghi, Federica; Fossati, Claudia; Giannelli, Stefania; Monti, Ilaria; Casiraghi, Miriam; Ferrua, Francesca; Recupero, Salvatore; Consiglieri, Giulia; Calbi, Valeria; Tucci, Francesca; et al. (Frontiers in Immunology, 2023)
Hemophagocytic inflammatory syndrome (HIS) is a rare form of secondary hemophagocytic lymphohistiocytosis caused by impaired equilibrium between natural killer and cytotoxic T-cell activity, evolving in hypercytokinemia and multiorgan failure. In the context of inborn errors of immunity, HIS occurrence has been reported in severe combined immunodeficiency (SCID) patients, including two cases of adenosine deaminase deficient-SCID (ADA-SCID). Here we describe two additional pediatric cases of ADA-SCID patients who developed HIS. In the first case, HIS was triggered by infectious complications while the patient was on enzyme replacement therapy; the patient was treated with high dose corticosteroids and intravenous immunoglobulins with HIS remission. However, the patient required HLA-identical sibling donor hematopoietic stem cell transplantation (HSCT) for definitive cure of ADA-SCID, without HIS relapse up to 13 years after HSCT. The second patient presented HIS 2 years after hematopoietic stem cell gene therapy (GT), secondarily to Varicella-Zoster vaccination and despite CD4 and CD8 lymphocytes’ reconstitution in line with other ADA SCID patients treated with GT. The child responded to trilinear immunosuppressive therapy (corticosteroids, Cyclosporine A, Anakinra). We observed persistence of gene corrected cells up to 5 years post-GT, without HIS relapse. These new cases of children with HIS, together with those reported in the literature, support the hypothesis that a major dysregulation in the immune system can occur in ADA-SCID patients. Our cases show that early identification of the disease is imperative and that a variable degree of immunosuppression could be an effective treatment while allogeneic HSCT is required only in cases of refractoriness. A deeper knowledge of immunologic patterns contributing to HIS pathogenesis in ADA-SCID patients is desirable, to identify new targeted treatments and ensure patients’ long-term recovery.